A multi-objective optimization model of component selection in enterprise information system integration - Mu, Lifeng; Kwong, C.K. (Computers & industrial engineering, 2018)
•Couplings and cohesions.•IT architecture multi-objective optimization.•Sensitive analysis. Integrating legacy IT assets and new commercial software components together into a flexible IT architecture is one of open challenges facing modern enterprises today. Most of previous studies focused on using re-engineering to improve the flexibility of IT architectures, rather than employing optimization theory in architecture design problem, especially the problem of component selection and re-allocation in IT architecture. Moreover, a scant amount of literature is available on considering the architectural flexibility and integration cost simultaneously. To fill in this gap, based on a modified quantitative method of measuring the relationship between couplings and cohesions in architecture, we devise a nonlinear multi-objective binary integer programming to select components from legacy candidates and commercial candidates, and to group them into services under the service-oriented architecture (SOA) environment. The customized SPEA2 algorithm is further used to solve the problem, and some managerial insights are provided based on experiments and sensitivity analysis with the model.